Efektivitas Penerapan Metode Mau’izhah dalam Meningkatkan Karakter Disiplin Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMP Pancasila Kota Bengkulu - Dori Setiawan (UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to determine the effectiveness of the Mau’izhah method used to improve student discipline in student learning at Pancasila Junior High School Bengkulu City. The research used a combination research approach (Mixed Methods) with a sequential explanatory design type, with a population of 35 students and teachers. Data collection methods used are questionnaires, interviews and documentation. After being analyzed with simple linear regression quantitative analysis, the results showed that the application of the mau’izhah method was effective in improving the discipline character of students at Pancasila Junior High School Bengkulu City, the partial t value was 2.975 with a significance of 5% > from t table 2.042. The Mau’izhah method is used to improve student discipline at SMP Pancasila City Bengkulu, contributing 21.10%, and the results of qualitative data analysis show that the mau’izhah method is said to be effective in improving student learning discipline, this can be seen from the results of the application of the method. what the teacher does in the learning process and outside of class hours is responded well by students, the results of the response are a lot of changes that occur to students such as students who were often late in coming in, have begun to gradually change, students who were often noisy in class now has begun to be orderly in carrying out learning, and students’ attitudes towards teachers have begun to reflect good students and even students’ interest in learning has increased.